Influence of Moisture Content, Loading Rate and Internode Position on the Mechanical Properties of Paddy and Wheat Straw - Muzamil, Mohd.; Mani, Indra; Kumar, Adarsh; Lande, Satish (International Journal of Bio-resource and Stress Management, 2023)
The mechanical characteristics of paddy straw and wheat Straw were evaluated in terms of shearing strength, specific shearing energy and cutting force with the change in moisture content, loading rate and inter node position. The parameters were determined at three moisture levels: 1%, 7.5% and 19.5% wb, three loading rates: 15, 20 and 25 mm. min-1 and three internodes: first (IN1), second (IN2) and third (IN3) position. The results showed that shear strength and specific shearing energy increased with an increase in moisture content and loading rate from first to third internode position. The shear strength of the paddy straw increased from 5.49 to 13.29, 6.28 to 14.69 and 6.98 to 18.26 MPa and for wheat straw 7.59 to 21.76, 8.16 to 23.8 and 8.77 to 24.8 MPa from first to third internode position. The corresponding value for specific shearing energy were 22.13 to 94.71, 29.86 to 115.6 and 35.02 to 158.6 mJ for paddy straw and 44 to 106.7, 49 to 101.3 and 54.3 to 119.3 mJ for wheat straw, respectively. The cutting force for paddy and wheat straw varied between 13.4 to 24.6 N and 14.8 to 27.5 N for different loading rates and at different inter node positions. Thus, variable load application at different inter node positions can ensure the saving of energy for harvesting and threshing machines.